Role of SV40 ST Antigen in the Persistent Infection of Mesothelial Cells - Fahrbach, Kelly M. (2007)
Viral DNA is maintained episomally in SV40 infected mesothelial cells and virus is produced at low but steady rates. High copy numbers of the viral DNA are maintained in a WT infection where both early antigens are expressed. In the absence of ST, cells are immortal but non-transformed and the infected cells maintain only a few copies of episomal viral DNA. We show that ST expression is necessary for the maintenance of high copy numbers of viral DNA and that the PP2A binding ability of ST plays a role in genome maintenance. Interestingly, an siRNA to the virus late region down regulates virus copy number and virus production but does not prevent the anchorage-independent growth of these cells. Furthermore, addition of virus neutralizing antibody to culture media also decreases copy numbers of viral DNA in WT-infected cells, suggesting that virus production and re-infection of cells may play a role in maintaining the persistent infection.